Enzyme-catalysed [4+2] cycloaddition is a key step in the biosynthesis of spinosyn A - Kim, Hak Joong; Ruszczycky, Mark W.; Choi, Sei-hyun; Liu, Yung-nan; Liu, Hung-wen (Nature (London), 2011)
A 'Diels–Alderase' enzyme identified The naturally occurring compound spinosyn A is a component of several environmentally benign commercial insecticides. How its tetracyclic ring system is biosynthesized has been a subject of much speculation. One possible mechanism is the Diels–Alder reaction, a [4+2] cycloaddition reaction in which a cyclohexene ring is formed between a conjugated diene and an electron-deficient alkene via a single pericyclic transition state. This reaction is a rarity in nature, but a structural and kinetic study of the enzyme SpnF from the soil bacterium Saccharopolyspora spinosa now identifies it as perhaps the first stand-alone enzyme to merit the name 'Diels–Alderase', solely committed to the catalysis of a [4+2] cycloaddition reaction with an estimated 500-fold rate enhancement. The Diels–Alder reaction is a [4+2] cycloaddition reaction in which a cyclohexene ring is formed between a 1,3-diene and an electron-deficient alkene via a single pericyclic transition state 1 . This reaction has been proposed as a key transformation in the biosynthesis of many cyclohexene-containing secondary metabolites 2 , 3 , 4 , 5 . However, only four purified enzymes have thus far been implicated in biotransformations that are consistent with a Diels–Alder reaction, namely solanapyrone synthase 6 , LovB 7 , 8 , macrophomate synthase 9 , 10 , and riboflavin synthase 11 , 12 . Although the stereochemical outcomes of these reactions indicate that the product formation could be enzyme-guided in each case, these enzymes typically demonstrate more than one catalytic activity, leaving their specific influence on the cycloaddition step uncertain. In our studies of the biosynthesis of spinosyn A, a tetracyclic polyketide-derived insecticide from Saccharopolyspora spinosa 13 , 14 , we identified a cyclase, SpnF, that catalyses a transannular [4+2] cycloaddition to form the cyclohexene ring in spinosyn A. Kinetic analysis demonstrates that SpnF specifically accelerates the ring formation reaction with an estimated 500-fold rate enhancement. A second enzyme, SpnL, was also identified as responsible for the final cross-bridging step that completes the tetracyclic core of spinosyn A in a manner consistent with a Rauhut–Currier reaction 15 . This work is significant because SpnF represents the first example characterized in vitro of a stand-alone enzyme solely committed to the catalysis of a [4+2] cycloaddition reaction. In addition, the mode of formation of the complex perhydro- as -indacene moiety in spinosyn A is now fully established.